Zonation and Associations of Dominant Fish Fauna on Flemish Cap - Paz, Xabier; Casas-Sánchez, José Miguel (1996)
Data were obtained from 682 demersal trawls made between 126 and 738 m depths on Flemish Cap in summer during the European Union research surveys in the years 1989–94. Despite the fact that the depth range for all species was not completely covered, analysis of different deep distributions of the 25 most representative species showed that the fauna are zoned with depth. Three faunal assemblages with characteristic catch rates, diversity and dominant species were found on the shelf (126–300 m), upper continental slope (300– 600 m) and middle continental slope (>600 m). Catch rates were greatest on the shelf and upper continental slope, while diversity was greatest on the middle continental slope. Dominance of the commercial species Atlantic cod (Gadus morhua), golden redfish (Sebastes marinus) and American plaice (Hippoglossoides platessoides) on the shelf, beaked redfish (Sebastes mentella) and Labrador redfish (Sebastes fasciatus) on upper continental slope, and Greenland halibut (Reinhardtius hippoglossoides) on the middle continental slope. This showed an important aspect of the community structure. Diversity patterns may be understood in terms of the relationships with predation, competition, environmental heterogeneity and trophic level. Also the influence of the fisheries in the area can modify this structure. On the size-depth correlations, only longnose eel (Synaphobranchus kaupy), longfin hake (Urophycis chestery), Atlantic cod (Gadus morhua), beaked redfish (Sebastes mentella), golden redfish (Sebastes marinus) and Greenland halibut (Reinhardtius hippoglossoides) showed a significant 'bigger-deeper' relationship (i.e. larger fish in deeper strata), while spotted wolffish (Anarhichas minor) and witch flounder (Glyptocephalus cynoglossus) showed a negative 'smaller-deeper' relationship.